Karya Roh Kudus Mengerjakan Mujizat Bagi Orang Kristen Pada Masa Kini - Sulistyoadi, Didik (Sekolah Tinggi Teologi Berita Hidup, 2024)
The postmodernism with its infatuation with spiritism has dragged the contemporary church towards the pursuit of miracles in the Christianity, and unfortunately it deviates a lot from the theological nature of the miracle itself. The purpose of this paper is to explain theologically the role of the Holy Spirit in miracles and its relation to believers. At the end of the article, the truth is found that miracles and the gift of performing miracles still occur today. Miracles are performed by the Holy Spirit through believers to fulfill God's purpose to build the body of Christ. Even though miracles have an important role in the task of building the body of Christ in this world, excessive pursuit of this will be bad for both the church itself and for the continuity of the universe.Keywords: Holy Spirit; miracles, Christian